World poverty and human rights - Pogge, Thomas Winfried Menko (Cambridge : Polity, 2008)
Thomas Pogge tries to explain how most of the population of this planet can excuse world poverty. A mere one or two % of the wealth of the richer nations could help in eradicating much of the poverty but there's a slim chance of that happening.
Human flourishing and universal justice -- How should human rights be conceived? -- Loopholes in moralities -- Moral universalism and global economic justice -- The bounds of nationalism -- Achieving democracy -- Cosmopolitanism and sovereignty -- Eradicating systemic poverty : brief for a global resources dividend -- Pharmaceutical innovation : must we exclude the poor?
Previous edition: 2002.
Includes bibliographical references (pages [265] -327) and index.
Keywords: Human rights; Poverty; Human Rights; Poverty; Droits de l'homme (Droit international); Poverty